2015
DOI: 10.1007/s12028-015-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Spontaneous Hyperventilation, Delayed Cerebral Ischemia, and Poor Neurological Outcome in Patients with Subarachnoid Hemorrhage

Abstract: Spontaneous hyperventilation is common in SAH and is associated with DCI and poor neurological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
7
31
2
2
Order By: Relevance
“…Williamson et al reported that severe hypocapnia, which was defined as PaCO 2 ≤ 30 mmHg, was significantly associated with poor neurological outcomes (OR, 4.52; p < 0.01) [15], and this finding is consistent with our result. However, they reported that moderate hypocapnia, which was defined as PaCO 2 < 35 mmHg, was not independently associated with poor neurological outcomes (OR, 1.30; p = 0.58) [15]. Hypocapnia was previously shown to be associated with brain tissue hypoxia and poor outcomes in patients with TBI [26, 27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Williamson et al reported that severe hypocapnia, which was defined as PaCO 2 ≤ 30 mmHg, was significantly associated with poor neurological outcomes (OR, 4.52; p < 0.01) [15], and this finding is consistent with our result. However, they reported that moderate hypocapnia, which was defined as PaCO 2 < 35 mmHg, was not independently associated with poor neurological outcomes (OR, 1.30; p = 0.58) [15]. Hypocapnia was previously shown to be associated with brain tissue hypoxia and poor outcomes in patients with TBI [26, 27].…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies reported that hypocapnia was associated with poor neurological outcomes or DCI [14, 15]. Williamson et al reported that severe hypocapnia, which was defined as PaCO 2 ≤ 30 mmHg, was significantly associated with poor neurological outcomes (OR, 4.52; p < 0.01) [15], and this finding is consistent with our result. However, they reported that moderate hypocapnia, which was defined as PaCO 2 < 35 mmHg, was not independently associated with poor neurological outcomes (OR, 1.30; p = 0.58) [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A few very interesting randomized trials are currently investigating neurocritical care measures beyond neurosurgery in or including SAH: EARLYDRAIN on early lumbar drainage combined with EVD [9], SETPOINT2 on early tracheostomy [10], NEWTON on slow-release nimodipine via EVD [11], ULTRA on early tranexamic acid [12], and HIMALAIA on induced hypertension [13]. However, there are so many other NCCU aspects to be addressed prospectively: level of sedation, modes of ventilation [14,15], cardiopulmonary stability [16,17], monitoring-based circulatory strategies [18], temperature control [19][20][21], delirium management, the nursing factor and mobilization, policies of do-not-resuscitate orders and withdrawal of care [22,23], and many other day-to-day care decisions that may substantially impact outcome. Particularly, the poor-grade SAH patient, prone to so many cerebral and systemic complications, may benefit from aggressive surveillance, superb nursing care, and close clinical monitoring.…”
mentioning
confidence: 99%
“…Such factors will need to be considered in future studies exploring pathophysiologic pathways, understanding that the impact of a pathway may be exacerbated or attenuated over time post insult based on such endogenous responses. For example cerebral ischemia/acidosis begets spontaneous hyperventilation ( 77 80 ) and systemic hypertension is a typical concomitant of brainstem ischemia ( 81 ). Other examples include ischemia-mediated adjustments in protein transcription and ischemic preconditioning ( 82 90 ) and issues in resilience or plasticity of pathophysiological networks, e.g., apoptosis networks ( 91 , 92 ).…”
Section: Discussionmentioning
confidence: 99%